Intellectual Capital and Bank Productivity: The Moderating Role of Risk Management in Indonesia and Malaysia - Damayanti, Desi Fitria; Pratama, Bima Cinintya; Fakhruddin, Iwan; Inayati, Nur Isna (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to analyze the effect of intellectual capital on bank productivity and the role of risk management as a moderating variable in the banking industry in Indonesia and Malaysia. The components of intellectual capital examined include human capital, structural capital, and physical capital (capital employed), with a total sample of 162 data from 59 banks selected using purposive sampling techniques during the period 2021-2023. The results indicate that human capital has a positive influence on bank productivity, while structural capital and physical capital show a negative influence. Additionally, risk management was found to have a negative influence on bank productivity, suggesting that overly stringent risk management approaches may hinder the optimal utilization of resources. These findings have important implications for the management of intellectual resources and risk in improving the competitiveness and performance of the banking sector, for example in the ASEAN region, such as Indonesia and Malaysia.